Pharmacokinetic and bioequivalence study of Telzap® in comparison with Mikardis® in healthy subjects after single administrationl - A. L. Khokhlov; A. A. Khokhlov; A. E. Miroshnikov; O. V. Lebedeva; D. Yu. Grebenkin (Фармакокинетика и Фармакодинамика, 2023)
Introduction. Telmisartan is widely used in clinical practice during hypertension treatment. It is a specific angiotensin II receptor antagonist (type AT1), effective at oral intake, A bioequivalence study of Telzap® and Mikardis® was conducted with 60 volunteers.Aim. The purpose of the bioequivalence trial was a comparative study of the pharmacokinetics and evidence of the bioequivalence of Mikardis® (telmisartan, tablets 80 mg, Boehringer Ingelheim International GmbH, Germany) and Telzap® (telmisartan, tablets 80 mg, Zentiva KS company, Czech Republic) in healthy volunteers after a single administration under fasting.Materials and methods. To prove bioequivalence, an open label, comparative, randomized, crossover four-period replicate single-center clinical trial was conducted. The concentrations of telmisartan in plasma samples were determined by a validated HPLC-MS/MS method. A pharmacokinetic and statistical analysis was performed and confidence intervals for the pharmacokinetic parameters Cmax and AUC0-72 were calculated.Results and discussion. It can be concluded that the studied formulations are bioequivalent in terms of pharmacokinetic parameters of test and reference drug. All 90 % confidence intervals of were within the bioequivalence range of 80–125 % for AUC0-72 and 73,07–136,85 % for Cmax.Conclusion. Thus, according to the criteria used in the study, the formulations are proved to be bioequivalent.